Metabolic and bariatric surgery among patients with social anxiety disorder, a matched cohort study - Jesper Christiansen; Erik Näslund; Henrik Larsson; Erik Stenberg (PLoS ONE, 2026)
Social anxiety disorder is common among patients considered for metabolic and bariatric surgery (MBS). The combination of social anxiety with obesity may, however, be associated with a higher risk for adverse outcomes after surgery. In this nationwide, registry-based, matched cohort study, all patients who underwent primary MBS in Sweden from 2007 until 2019 and who had a diagnosis of moderate to severe social anxiety disorder (n = 586) were matched using a Propensity score to controls who underwent the same treatment but who did not have social anxiety disorder (n = 5791) with a mean follow-up time of 6.9 years. Patients with social anxiety disorder experienced an increased risk for non-serious postoperative complications (OR 1.59; 95%CI 1.21–2.09), self-harm (HR 2.44 CI 95% 1.84–3.25 p < 0.001) and alcohol or substance abuse (HR 2.41, 95%CI 1.96–2.96, p < 0.001), and reported lower psychosocial health-related quality of life before and after surgery. However, patients with social anxiety disorder significantly improved in health-related quality of life compared to baseline, and experienced similar effects on weight reduction at 2 years after surgery (total weight loss: 32.8 ± 10.3% compared to 32.6 ± 9.7%) and risks for cardiovascular events compared to the matched control group. MBS appears to be a safe and effective treatment for severe obesity in patients with social anxiety disorder, but an individualized and increased peri- and postoperative support should be considered for patients with moderate to severe social anxiety disorder and severe obesity.